2010
DOI: 10.1007/s10551-010-0703-y
|View full text |Cite
|
Sign up to set email alerts
|

CSR and Service Brand: The Mediating Effect of Brand Identification and Moderating Effect of Service Quality

Abstract: service brand loyalty, corporate associations, CSR, brand identification, service quality, customer satisfaction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
385
1
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(437 citation statements)
references
References 79 publications
(134 reference statements)
32
385
1
19
Order By: Relevance
“…Numerous studies have confirmed the influence of perceptions about CSR dimensions on customers' loyalty (Ailawadi et al, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Numerous studies have confirmed the influence of perceptions about CSR dimensions on customers' loyalty (Ailawadi et al, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Customers have more trust, purchase more, and prefer to recommend socially responsible companies (Vlachos, Tsamakos, Vrechopoulos, & Avramidis, 2009). Numerous studies have shown a positive relationship between perceptions of CSR and customer loyalty (Ailawadi, Neslin, Luan, & Taylor, 2014;Chung et al, 2015;García de los Salmones et al, 2005;He & Li, 2011;Lee et al, 2012;Marin et al, 2009;Perez et al, 2012;Srbljinović, 2012). Customers appreciate companies' participation in humanitarian events, programs devoted to energy conservation, sponsorship of local events, etc.…”
Section: Economic Responsibilitiesmentioning
confidence: 99%
“…A social identity perspective has been found effective in establishing brand loyalty in various service contexts such as banking, (He and Li 2011). However, the same has not been examined in context of the hotel industry, despite that fact that this industry is heavily dependent on customer trust and loyalty toward the hotel brand.…”
Section: Fatma and Rahman: Perceived Ethicality Influences On Brand Lmentioning
confidence: 99%
“…"Identification-based trust" refers to the people's identification with the brand through social norm, rather than past connection or experience (Creed and Miles 1996). Brand identification enables positive consumer evaluation of the brand (He and Li 2011); when customer expectations regarding brand performance are confirmed or exceeded, the identified customers feel a psychological attachment to the brand (Marin et al 2009). …”
Section: Brand Identification and Brand Trustmentioning
confidence: 99%
“…In what concerns service industries, in which case customer loyalty is more elusive and unpredictable as compared to other sectors (Vlachos and Vrechopoulos, 2012), most studies have been focused on industries such as: retail (Ailawadi et al, 2014, Gupta and Pirsch, 2008, Lombart and Louis, 2014, Vlachos, 2012, Vlachos and Vrechopoulos, 2012, Walsh and Bartikowski, 2013, banking (Choi and La, 2013, Chomvilailuk and Butcher, 2014, Mandhachitara and Poolthong, 2011, Marin et al, 2009, Matute-Vallejo et al, 2011, Salmones et al, 2009, Walsh and Beatty, 2007, and telecom (He and Li, 2011, Moisescu, 2015a, Salmones et al, 2005, Vlachos et al, 2009.…”
Section: The Relationship Between Customer-based Perceptual Csr and Cmentioning
confidence: 99%